2018
DOI: 10.3354/aei00260
|View full text |Cite
|
Sign up to set email alerts
|

Changes in water temperature and oxygen: the effect of triploidy on performance and metabolism in large farmed Atlantic salmon

Abstract: In salmon farming, the use of sterile triploids (3N) can mitigate the problem of escapees interbreeding with wild salmon. However, triploid salmon appear less tolerant to high water temperatures and low oxygen levels compared to diploids (2N). To investigate how the thermal performance and physiology of large (2.5 kg) triploid Atlantic salmon Salmo salar L. differs from those of diploids, both ploidies were subjected to water temperatures between 3 and 18°C. The fish were exposed to reduced oxygen saturations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 68 publications
(102 reference statements)
2
30
0
Order By: Relevance
“…These morphometric differentiations may be considered as a compensation mechanism finally resulting in similar haemoglobin concentrations between the ploidy levels. The present data are in accordance to a study on O. mykiss and S. fontinalis (Benfey & Biron, ), while reduced haemoglobin concentrations were reported in peripheral blood of triploid S. salar (Graham, Fletcher, & Benfey, ; Sambraus et al, ) and O. tshawytscha (Bernier et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These morphometric differentiations may be considered as a compensation mechanism finally resulting in similar haemoglobin concentrations between the ploidy levels. The present data are in accordance to a study on O. mykiss and S. fontinalis (Benfey & Biron, ), while reduced haemoglobin concentrations were reported in peripheral blood of triploid S. salar (Graham, Fletcher, & Benfey, ; Sambraus et al, ) and O. tshawytscha (Bernier et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…However, at 19°C triploids could not metabolize phosphocreatine and regenerated ATP slower than diploids (Hyndman, Kieffer, & Benfey, ). In adult triploid Atlantic salmon ( S. salar ) muscle energy phosphates were generally lower than in diploids (Sambraus et al, ). Additionally, muscle glucose and blood haemoglobin concentrations were decreased at elevated temperatures (Sambraus et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these advantages, triploidy has yet to become widely adopted in salmon aquaculture because in stressful environments (e.g., high temperature, hypoxia, and exhaustive exercise), triploids perform poorly compared to their diploid counterparts (Hyndman et al 2003a;Hansen et al 2015;Sambraus et al 2017a;Sambraus et al 2018). Therefore, many studies have attempted to find physiological differences between triploids and diploids, as pinpointing such differences could allow for aquaculture practices to compensate for them.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for why triploidy influences performance is that fundamental changes in their cell size and number (Benfey 1999) affect metabolic processes under suboptimal conditions to a greater extent than in diploids. For instance, while numerous studies have not found a significant effect of triploidy on standard or routine metabolic rates (SMR and RMR, respectively) at or near optimum temperatures for diploids (Sezaki et al 1991;Parsons 1993;Hyndman et al 2003b;Bernier et al 2004;Lijalad and Powell 2009;Bowden et al 2018), experiments conducted at higher temperatures suggest that triploids have a lower thermal optimum for metabolism than diploids (Atkins and Benfey 2008;Sambraus et al 2017a;Sambraus et al 2018). Routine metabolic rate is the metabolic rate of a fish in a post-absorptive state that is experiencing routine (but minimal) periods of activity; RMR is distinguished from SMR in that measurements taken during minor activity are included, whereas SMR involves protocols to exclude periods of significant activity (Chabot et al 2016a).…”
Section: Introductionmentioning
confidence: 99%